The neural control mechanisms underlying memory-guided attention - Gould, I; Stokes, M; Atherton, K; Nobre, A (Springer Nature, 2009)
The control mechanisms that guide selective attention are typically examined in response to explicit attentional cues. In everyday life, however, the focus of attention is more typically guided according to past experiences than direct instruction. We therefore developed a novel behavioural paradigm to examine the neural substrate of memory-guided attentional orienting. Participants first learn the location of target stimuli hidden within naturalistic scenes. After the target locations have been learned, participants then perform an attention-orienting task. Each experimental trial begins with a cue stimulus, consisting of the memory scene presented without the target stimulus. A test scene is then presented, with a 50% probability of a target stimulus being present at the remembered location. Participants are instructed to use their memories to guide the focus of attention. In a previous fMRI study (Summerfield et al., 2006, Neuron), trials involving memory-guided attention were shown to engage activity in the same dorsal frontoparietal network that is typically associated with explicitly cued shifts of spatial attention, and in the hippocampus. However, it was not possible to isolate target-related processes from cue-related processes. In the present study, we tested and verified the roles of dorsal frontoparietal cortex and hippocampus activity in the neural control of memory-guided attention, by dissociating mnemonic cue-related activity from target-related activity. These results provide additional insights into the functional neural architecture of memory-guided attention, broadening the neuroscientific foundations for a more generalised account of attentional control during real-world behaviour.